UNLP experiences to reduce the digital gap - Harari, Viviana
For several years, the Computer Science Faculty at the National University of La Plata, Argentina, has established as one of its main goals to approach the various sectors of the community. The Faculty has worked actively to reduce the digital gap in our society. During the last two years the Faculty has dictated courses for elder adults (along with the Council for the Third Age in the city of La Plata). It has also dictated workshops and updating courses on Networks and Open Source Software for teachers of diverse scholarly levels (there are ten collaboration agreements with schools of different levels). In order to deepen this strategy, actions have been focused on young people in critical situations regarding their qualifications and the possibility of acceding to a dignifying job. The Computer Science Faculty, through its Extension Secretariat, along with the Association Center for Childhood (Asociación Centro Para la Niñez - Aso.Ce.Pa.Ni), organized and dictated a basic computer science training course for a group of young people (ages between 15 and 22 years old) who assist to different community dining rooms from that Association. The experience was very interesting, for it was the first time that our institution worked with that student profile. This training gave the students a new alternative for a quick job search, but it had an additional accomplishment for our institution: to come closer to high schools. The topics and the way they would be carried out in the courses were revised. Exercises were formulated in order to be alike those situations required in different organizations, so that the students could later confront real work conditions. The objective of this article it to describe this experience, the methodology which was put in practice, the contents and the different evaluations imparted during the course. This experience made it possible for the University to come closer to a sector of the community that is excluded from the information society.